Cancer Stem Cell and Tumor Immune Microenvironment (TIME): Dangerous Crosstalk - Moussa, Salim (Current Molecular Medicine, 2025)
Cancer stem cells (CSCs) are the key drivers of tumorigenesis and relapse. A growing body of evidence reveals the tremendous power of CSCs to directly resist innate and adaptive anti-tumor immune responses. The immunomodulatory property gives CSCs the ability to control the tumor immune microenvironment (TIME). CSCs hijack the anti-tumor capacity of immune cells to provide self-protection from immune attack and enhance the pro-tumor immune cell infiltration and activity. To date, cancer immunotherapy strategies have largely been designed without taking into account the immunosuppressive properties of CSCs. As a result, the clinical efficacy of cancer immunotherapy is altered, perpetuating tumor progression and relapse. Therefore, targeting the signals underlying CSC immune evasion is essential to improve immunotherapy efficacy and reduce tumor relapse. The aim of this mini-view is to comprehensively summarize the key immune escape mechanisms adopted by CSCs. This will provide necessary clues for the development of more effective cancer immunotherapy strategies.
Keywords: signals